DNA base trimers: empirical and quantum chemical ab initio calculations versus experiment in vacuo - Kabeláč, Martin; Sherer, Edward C; Cramer, Christopher J; Hobza, Pavel (Chemistry, 2007)
A complete scan of the potential-energy surfaces for selected DNA base trimers has been performed by a molecular dynamics/quenching technique using the force field of Cornell et al. implemented in the AMBER7 program. The resulting most stable/populated structures were then reoptimized at a correlated ab initio level by employing resolution of the identity, Moller-Plesset second-order perturbation theory (RI-MP2). A systematic study of these trimers at such a complete level of electronic structure theory is presented for the first time. We show that prior experimental and theoretical interpretations were incorrect in assuming that the most stable structures of the methylated trimers corresponded to planar systems characterized by cyclic intermolecular hydrogen bonding. We found that stacked structures of two bases with the third base in a T-shape arrangement are the global minima in all of the methylated systems: they are more stable than the cyclic planar structures by about 10 kcal mol(-1). The different behaviors of nonmethylated and methylated trimers is also discussed. The high-level geometries and interaction energies computed for the trimers serve also as a reference for the testing of recently developed density functional theory (DFT) functionals with respect to their ability to correctly describe the balance between the electrostatic and dispersion contributions that bind these trimers together. The recently reported M052X functional with a polarized triple-zeta basis set predicts 11 uracil trimer interaction energies with a root-mean-square error of 2.3 kcal mol(-1) relative to highly correlated ab initio theoretical calculations.
Keywords: Hydrogen Bonding; financování organizované; konformace nukleové kyseliny; chemické modely; Financing, Organized; Chemistry, Physical; DNA; Models, Chemical; vodíková vazba; Nucleic Acid Conformation; fyzikální chemie